Lattice Softening Significantly Reduces Thermal Conductivity and Leads to High Thermoelectric Efficiency - Hanus, Riley; Agne, Matthias T.; Rettie, Alexander J. E.; Chen, Zhiwei; Tan, Gangjian; Chung, Duck Young; Kanatzidis, Mercouri G.; Pei, Yanzhong; Voorhees, Peter W.; Snyder, G. Jeffrey (Advanced materials (Weinheim), 2019)
The influence of micro/nanostructure on thermal conductivity is a topic of great scientific interest, particularly to thermoelectrics. The current understanding is that structural defects decrease thermal conductivity through phonon scattering where the phonon dispersion and speed of sound are assumed to remain constant. Experimental work on a PbTe model system is presented, which shows that the speed of sound linearly decreases with increased internal strain. This softening of the materials lattice completely accounts for the reduction in lattice thermal conductivity, without the introduction of additional phonon scattering mechanisms. Additionally, it is shown that a major contribution to the improvement in the thermoelectric figure of merit (zT > 2) of high‐efficiency Na‐doped PbTe can be attributed to lattice softening. While inhomogeneous internal strain fields are known to introduce phonon scattering centers, this study demonstrates that internal strain can modify phonon propagation speed as well. This presents new avenues to control lattice thermal conductivity, beyond phonon scattering. In practice, many engineering materials will exhibit both softening and scattering effects, as is shown in silicon. This work shines new light on studies of thermal conductivity in fields of energy materials, microelectronics, and nanoscale heat transfer. Two fundamentally different avenues for controlling thermal conductivity are phonon scattering and lattice softening, or the reduction of phonon speed. The latter mechanism is particularly attractive when phonon–phonon scattering is inherently very strong, such as in thermoelectric materials and/or at high temperatures. In this work, the importance of lattice softening is shown in two specific cases, PbTe and nanocrystalline Si.